Collective animal navigation and migratory culture: from theoretical models to empirical evidence. (26th March 2018) - Berdahl, Andrew M.; Kao, Albert B.; Flack, Andrea; Westley, Peter A. H.; Codling, Edward A.; Couzin, Iain D.; Dell, Anthony I.; Biro, Dora
Abstract : Animals often travel in groups, and their navigational decisions can be influenced by social interactions. Both theory and empirical observations suggest that such collective navigation can result in individuals improving their ability to find their way and could be one of the key benefits of sociality for these species. Here, we provide an overview of the potential mechanisms underlying collective navigation, review the known, and supposed, empirical evidence for such behaviour and highlight interesting directions for future research. We further explore how both social and collective learning during group navigation could lead to the accumulation of knowledge at the population level, resulting in the emergence of migratory culture. This article is part of the theme issue 'Collective movement ecology'.